Determination of the minimal clinically important difference for seven measures of fatigue in Swedish patients with systemic lupus erythematosus. (May 2015) - Pettersson, S; Lundberg, IE; Liang, MH; Pouchot, J; Welin Henriksson, E
<x xml:space="preserve">Abstract</x> Objective: To estimate the minimal clinically important difference (MCID) in seven self-administered measures assessing fatigue in Swedish patients with systemic lupus erythematosus (SLE). Method: The participants (n = 51, women 98%, age 52.8 ± 12.1 years, disease duration 18.7 ± 13.6 years) met in groups of six to nine persons. After completing seven fatigue questionnaires [the Fatigue Severity Scale (FSS); the Multidimensional Assessment of Fatigue (MAF) scale; the 20-item Multidimensional Fatigue Inventory (MFI); the Chalder Fatigue Scale (CFS); the Short Form-36 Vitality subscale (VT); the Functional Assessment of Chronic Illness Therapy – Fatigue (FACIT-F) scale; and the Numeric Rating Scale (NRS)], each respondent had a minimum of five face-to-face discussions, followed by an individual comparative assessment of their own level of fatigue (seven-grade scale). This method resulted in 260 contrasting assessments; MCIDs were first calculated using the paired differences and then established by a regression approach. Patients were asked to comment on their experience with the questionnaires and whether they captured their fatigue adequately. Results: The paired approach (using 'little more fatigue' as an anchor for MCID during the face-to-face comparative assessments) provided estimates of 4.6–17.0; the regression approach provided estimates of 4.3–10.8. Estimates using the regression approach were consistently lower than those using the paired model. The MCID estimates were least favourable and fewer respondents supported the use of the NRS compared to the other self-reported questionnaires. Conclusions: All seven instruments detect MCIDs for fatigue in Swedish patients with SLE. However, the single-question measure was not supported by the MCID estimates or by comments from the respondents.